Influência da família na especialização precoce de atletas de alto rendimento - Zangotti, Lucas Gabriel [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The early sport specialization is a topic that has been widely debated for a long time, with diverse opinions about its benefits and harms, especially in certain sport modalities where the subjects career is short and the high level is reached early, disrespecting some human development factors. Thus, the objective of the study was to analyze the influence that relatives have on their children or other relatives. The study was based on a research method aimed at documentary and bibliographic review, using published scientific articles (in magazines, periodicals or electronic media), newspapers, books, reports, news, among other materials that approach the content and provide further discussion of the work. In this way, we were able to encounter the real existence of the early sport specialization in athletes in the present day, and that can occure due to factors that influence the family members, especially the parents, since they have the first social contact with their children, who can become sportsmen in the future. In addition, we noted that parents can influence both positivly and negatively in various aspects of their childrens lives, either in the sporting context or outside it, leading to series of emotional (psychological) alterations as well as physical, motor, and cognitive impairments, especially when allied with the work done in an wrong way by the trainer, not respecting the particularities of the individuals, nor their growth stages. Thus, after the review carried out in this study, it could be considered that early sports specialization is a risk that several children encounter, being important the role of the parents in the sense of support with the formation of the individual and not seeking to achieve their frustrated dreams and deposit all the hopes in the sports career of their children. It is important that parents follow some norms / suggestions to properly handle and help their...

A especialização esportiva precoce é uma temática bastante debatida desde um período antigo, possuindo opiniões diversas sobre seus benefícios e malefícios, principalmente em determinadas modalidades esportivas onde a carreira é curta e o alto nível é alcançado precocemente, desrespeitando alguns fatores maturacionais importantes ao desenvolvimento humano. Sendo assim, o objetivo do presente estudo é analisar a influência que os familiares possuem sobre seus filhos ou outros parentes. O estudo contou com o método de pesquisa voltado para revisão documental e bibliográfica, utilizando artigos científicos publicados (tanto em revistas, periódicos ou meios eletrônicos), jornais, livros, reportagens, notícias, dentre outros materiais que abordem o conteúdo e proporcionem maior aprofundamento à discussão do trabalho. Desta forma, pudemos evidenciar a real existência da especialização esportiva precoce em atletas nos dias atuais, podendo ocorrer por fatores que envolvem a influência dos familiares, principalmente dos pais, pois são essas figuras que possuem o primeiro contato social com as crianças/jovens que possam vir a ser esportistas no futuro. Além disso, notamos que os pais podem influenciar tanto positivamente quanto negativamente em diversos aspectos da vida de seus filhos, seja no contexto esportivo ou fora dele, podendo acarretar uma série de alterações emocionais (psicológicas), bem como danos físicos, motores e cognitivos, principalmente quando aliado com o trabalho realizado de maneira errônea por parte do treinador, não respeitando as particularidades dos indivíduos, nem suas devidas etapas maturacionais. Assim, após a revisão realizada neste estudo, pode-se considerar que a especialização esportiva precoce é um risco que diversas crianças correm, sendo importante o papel dos pais no sentido de corroborar com a formação do indivíduo e não buscar...
Keywords: Esportes - Aspectos psicológicos; Atletas; Profissionalismo nos esportes; Aptidão física do atleta; Família; Pais e filhos